Identifikasi status gizi, somatotipe, asupan makan dan cairan pada atlet atletik remaja di Indonesia - Mirza Hapsari Sakti Titis Penggalih; Mustika Cahya Nirmala Dewinta; Kurnia Mar'atus Solichah; Diana Pratiwi; Ibtidau Niamilah; Almira Nadia; Marina Dyah Kusumawati (Journal of Community Empowerment for Health, 2019)
Athletes’ nutrition status, somatotype, and adequate dietary intake are strongly related to their sport performance. Examining those markers in adolescent age is essential in order to develop the optimum physical characteristics for the future. This study was conducted to identify the nutrition status based on anthropometry value, somatotype, food and fluid intake of youth athletic athletes in Indonesia. Descriptive quantitative design was used in this study. Subjects participated in the study were 25 youth athletic athletes from Students Education and Training Program (Program Pembinaan dan Pelatihan Pelajar) in Yogyakarta and Aceh, and School of Sports (Sekolah Keolahragaan) Ragunan, Jakarta Selatan. Anthropometry measurement consists of body weight, height, body fat percentage, and somatotype. Nutrition status was identified according to BMI/age and height/age. Food and fluid intake were assessed using 24-hour dietary recall interview and semi quantitative fluid frequency questionnaire. Descriptive statistical analysis was performed and the result was presented in mean and standard deviation (SD). BMI/ age values in male and female athletes were -2 SD ≤ Z ≤ +1 SD (normal) and +1 SD < Z ≤ +2 SD (overweight), respectively. Height/age value for both gender was normal in -2 SD ≤ Z ≤ +2 SD. Percentage of body fat ranged in 12-16% for males and 18-28% for females. Somatotype category for males was ectomorphic mesomorph (2.3-5.0-3.3) and endomorphic mesomorph (4.4-5.6-2.0) for females. Fulfillment of energy and carbohydrate was found inadequate (< 80%), whereas fat intake was found excess (> 110%). Total fluid intake was ranged from 2700 ml to 5800 ml per day. Overweight nutrition status was still found in femaleathletes. Ideal somatotype was found only in male athletes. Excessive percentage of body fat was detected in both gender. Total energy, macro nutrients, micro nutrients, and fluid intake were inadequate compared to dietary recommendation.